Hybrid Dye-Titania Nanoparticles for Superior Low-Temperature Dye-Sensitized Solar Cells - Kunzmann, Andreas; Valero, Silvia; Sepulveda, Angel E.; Rico-Santacruz, Marisa; Lalinde, Elena; Berenguer, Jesus R.; Garcia-Martinez, Javier; Guldi, Dirk Michael; Serrano, Elena; Costa Riquelme, Rubén Dario (Advanced Energy Materials, 2018)
In this work, a new strategy to design low-temperature (≤200 °C) sintered dye-sensitized solar cells (lt-DSSC) is reported to enhance charge collection efficiencies (ηcoll), photoconversion efficiencies (η), and stabilities under continuous operation conditions. Realization of lt-DSSC is enabled by the integration of hybrid nanoparticles based on TiO2-Ru(II) complex (TiO2_Ru_IS)—obtained by in situ bottom-up construction of Ru(II) N3 dye-sensitized titania—into the photoelectrode. Incentives for the use of TiO2_Ru_IS are i) dye stability due to its integration into the TiO2 anatase network and ii) enhanced charge collection yield due to its significant resistance toward electron recombination with electrolytes. It is demonstrated that devices with single-layer photoelectrodes featuring blends of P25 and TiO2_Ru_IS give rise to a 60% ηcoll relative to a 46% ηcoll for devices with P25-based photoelectrodes. Responsible for this trend is a better charge transport and a reduced electron recombination. When using a multilayered photoelectrode architecture with a top layer based only on TiO2_Ru_IS, devices with an even higher ηcoll (74%) featuring a η of around 8.75% and stabilities of 600 h are achieved. This represents the highest values reported for lt-DSSC to date.
CRIS-Team Scopus Importer:2022-04-14
Keywords: charge collection efficiency; dye-sensitized solar cells; hybrid dye-titania nanoparticles; low temperature sintering; multilayered electrodes